THE USE–TRUST LOOP: REEL CULTURE, SEMI-NEWS NARRATIVES, AND CREDIBILITY IN HYPERLOCAL JOURNALISM - Dubey, Harsh Vardhan (ShodhKosh: Journal of Visual and Performing Arts, 2023)
The growing popularity of short-form video, or reels, has transformed the news ecosystem, particularly in regional contexts. This paper explores the relationship between frequency of reel use and perceptions of credibility—a dynamic conceptualized here as the use–trust loop. Drawing on a mixed-methods study conducted in Gorakhpur, India, the research combines survey responses from 200 participants, content analysis of 100 reels, and interviews with 12 founder-editors of hyperlocal outlets. Findings reveal that reel consumption is near-universal, with 92% of respondents watching daily, and that higher levels of use correspond to greater trust. Content analysis shows a significant presence of semi-news narratives, blending humor and information, which audiences find both engaging and credible. Platform hierarchies place YouTube and Instagram reels as more trusted than WhatsApp forwards, highlighting the mediating role of algorithms. The study concludes that credibility in reel-based journalism is constructed less through verification and more through repetition, presence, and community embeddedness. These insights contribute to ongoing debates about digital trust, infotainment, and the future of hyperlocal journalism in India.